(untitled) (Research, Society and Development, 2021)
The diazotrophic bacteria Azospirillum brazilense are beneficial for the plants due to the ability to break the molecule of N2, facilitating its assimilation by the plants, moreover, it is considered a promoter of vegetative growth, because they induce in the production and release of phytohormones such as auxins, gibberellins and cytokines, responsible for vegetative growth and expansion of the root system. Due to the species of Tento Carolina being widely used in urban arborization and in reforestation areas, the objective of this work was to evaluate the effect of the inoculation of Azospirillum brasilense, in different doses, in the development of seedlings of Tento Carolina (Adenanthera pavonina L.). The research was composed by an experimental design entirely randomized with six treatments, four repetitions and four plants per plot. The doses used were: T1: 0 ml (witness); T2: 0.3 ml; T3: 0.6 ml; T4: 0.9 ml; T5: 1.2 ml and T6: 1.5 ml) for 30 grams of seeds. The experiment was conducted in a green house in the municipality of Cáceres, MT. Morphological evaluations of the plants were performed 120 days after sowing. The data were submitted to computer program R, applying the F test for diagnosis of significant effect, and the means compared by the Tukey test at 5% probability. The results obtained indicate that there was a significant difference between the treatments using Azospirillum brasilense, and only for the variables of number of leaves and relation height of the aerial part/diameter of the collection its use was indifferent. No treatment with inoculant presented superior result to the treatment called witness.